2005
DOI: 10.1159/000090709
|View full text |Cite
|
Sign up to set email alerts
|

Double Dissociation of Hangul and Hanja Reading in Korean Patients with Stroke

Abstract: The orthographic system of the Korean language consists of both phonogram (Hangul) and ideogram (Hanja). We report 2 patients who revealed selective impairment in reading either of orthographies after the brain damages. YJ, a 67-year-old man, showed Broca’s aphasia and severe apraxia of speech after a stroke in the left inferior parietal lobe. He demonstrated predominant difficulties in reading phonogram. KS, a 51-year-old woman, had an intracerebral hemorrhage in the left parietal lobe. She showed anomic apha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
1
9
1
2
Order By: Relevance
“…In our patient, the competence of semantic knowledge of ideogram is quite similar to that of visual objects, suggesting that a common neural mechanism underlies the semantic recognition process for both ideogram and objects. Moreover, it may reflect the role of the right hemisphere in reading ideogram12 and supports the different processing of phonograms and ideograms in the Korean orthographic system 10,12…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In our patient, the competence of semantic knowledge of ideogram is quite similar to that of visual objects, suggesting that a common neural mechanism underlies the semantic recognition process for both ideogram and objects. Moreover, it may reflect the role of the right hemisphere in reading ideogram12 and supports the different processing of phonograms and ideograms in the Korean orthographic system 10,12…”
Section: Discussionmentioning
confidence: 67%
“…did not experience any problems in this test. The Korean orthographic system consists of both phonograms (Hangul) and ideograms (Hanja), and a double dissociation between the processing of the orthographies have been proposed 10. Thus, the tests for both Hangul and Hanja reading were performed.…”
Section: Case Reportmentioning
confidence: 99%
“…Transformation of Hangul graphemes into phonemes appears to occur in the AG, while transfer of Hanja graphemes occurs in the area of LSPC or BA7 (Fig. 4C, D) (1, 7, 11, 16, 17, 18, 19, 20, 21, 22) and then to the Broca's area (BA44, 45). In this scheme, the role of the LSPC is still unclear but it is one of the high visual association area believed to be responsible for high level visual information processing (10).…”
Section: Discussionmentioning
confidence: 99%
“…However, the anatomical lesions that resulted in selective Hangul reading impairment and characteristics of language disturbances in their patient were different from those of our patient. The patient in the previous study had an ischemic lesion of the left postcentral gyrus, the inferior parietal lobule, and the posterior insula and showed Broca's type of aphasia [4]. Due to the Broca's aphasia, the reading ability of the patient was assessed by matching words and objects, and by choosing the matched one among five words after listening to the word; this differs from the usual procedure such as reading aloud.…”
Section: Discussionmentioning
confidence: 99%
“…One case study reported a Korean patient with alexia and agraphia for Hanja but in-tact reading and writing for Hangul following a left posterior inferior temporal lobe infarction [3]. Another study showed a double dissociation of Hangul and Hanja reading and that the prominent alexia for Hangul was caused by an infarction in the left inferior parietal lobe, while the profound alexia for Hanja was caused by a cerebral hemorrhage in the left parietal lobe [4].…”
Section: Introductionmentioning
confidence: 99%